2021
DOI: 10.1007/s11661-021-06533-w
|View full text |Cite
|
Sign up to set email alerts
|

A Scale-up Study on Chemical Segregation and the Effects on Tensile Properties in Two Medium Mn Steel Castings

Abstract: Two ingots weighing 400 g and 5 kg with nominal compositions of Fe–8Mn–4Al–2Si–0.5C–0.07V–0.05Sn were produced to investigate the effect of processing variables on microstructure development. The larger casting has a cooling rate more representative of commercial production and provides an understanding of the potential challenges arising from casting-related segregation during efforts to scale up medium Mn steels, while the smaller casting has a high cooling rate and different segregation pattern. Sections fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…In order to simulate an industrial reheating cycle, the ingot was homogenised in a vacuum tube furnace at 1250 • C for 2 h and allowed to furnace cool to room temperature. A previous study [35] showed that the abovementioned homogenisation schedule was able to significantly reduce microsegregation in an arc melted ingot. The ingot was then reheated to 1100 • C and rough rolled at the same temperature from 23 to 12 mm thickness in 4 passes and water quenched.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…In order to simulate an industrial reheating cycle, the ingot was homogenised in a vacuum tube furnace at 1250 • C for 2 h and allowed to furnace cool to room temperature. A previous study [35] showed that the abovementioned homogenisation schedule was able to significantly reduce microsegregation in an arc melted ingot. The ingot was then reheated to 1100 • C and rough rolled at the same temperature from 23 to 12 mm thickness in 4 passes and water quenched.…”
Section: Methodsmentioning
confidence: 95%
“…This is enabled by a combination of either low Mn and high C (current alloy), or high Mn and low C. If the TWIP effect can be forgone during alloy design, it would be possible to enable low to medium Mn and low C (3-6 wt% Mn, 0.05-0.2 wt% C) compositions that exhibit the TRIP effect only. Such low Mn, low C compositions have been increasingly termed lean medium Mn steels [67], and are desirable in terms of lower segregation after casting [35], better weldability [68], processability, etc. However, it is worth noting that while the TWIP effect does little for TWIP + TRIP-type medium Mn steels, the tensile properties still tend to be better in terms of elongation than in pure TRIP-type medium Mn steels [19,26,27,69].…”
Section: Strain Hardening Behaviour and Constitutive Modellingmentioning
confidence: 99%
“…As previously mentioned, when cementite particles form in the microstructure, C is lost from the austenite phase which has the adverse effect of decreasing the SFE and increasing the Md 30 temperature (Figures 2 (d,g)). Voids also tend to form around cementite particles at high strains which may act as crack nucleation sites [92]. Therefore it is best to avoid cementite formation altogether.…”
Section: Carbonmentioning
confidence: 99%
“…The presence of δ -ferrite may also indicate non-equilibrium Scheil solidification where local compositions of Al and Si due to microsegregation are able to stabilise δ -ferrite. If reheated for a sufficiently long time for the diffusion of Al and Si, it may be possible for microsegregation related δ -ferrite to transform into austenite [92]. However, if the alloy chemistry is such that there is no fully austenitic region (Figure 3(b)), then δ -ferrite will always be present.…”
Section: Metallurgy Of Medium Mn Steelsmentioning
confidence: 99%
“…Calphadcoupled MMPF simulations have become state of the art for steel grades, e.g. [4][5][6][7][8][9][10][11][12][13][14][15][16] and recently also for solidification of cast irons [17][18][19]. A general complexity of iron-based alloys is that the primary solidification structure does not remain stable, but austenite decomposes into ferrite and cementite during further cooling.…”
Section: Introductionmentioning
confidence: 99%